RETRACTED: The role and practical significance of interesting issues in the development of students’ cognitive competencies - Turaev Khumoyiddin; Yadgarov Nadir; Mamatov Dilshod (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001